2001
DOI: 10.18388/abp.2001_3907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth at low temperature on the alternative pathway respiration in Acanthamoeba castellanii mitochondria.

Abstract: Mitochondria of amoeba Acanthamoeba castellanii in addition to the conventional cytochrome pathway possess, like plant mitochondria, a cyanide-resistant alternative quinol oxidase. In mitochondria isolated from amoeba batch culture grown temporarily at low temperature (6 degrees C), higher respiration was accompanied by lower coupling parameters as compared to control culture (grown at 28 degrees C). In the presence of benzohydroxamate, respiratory rates and coupling parameters were similar in both types of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…This role could become especially important when the ROS level increases [14][15][16]. Therefore, the data presented in this work are consistent with our previous results showing that the activity and protein level of both, AcAOX and AcUCP, is enhanced by growth of amoeba cells in low temperature that is likely to be accompanied by a higher cellular ROS generation [11,12].…”
Section: Physiological Role Of Acucp and Acaox As Antioxidant Defensesupporting
confidence: 92%
See 1 more Smart Citation
“…This role could become especially important when the ROS level increases [14][15][16]. Therefore, the data presented in this work are consistent with our previous results showing that the activity and protein level of both, AcAOX and AcUCP, is enhanced by growth of amoeba cells in low temperature that is likely to be accompanied by a higher cellular ROS generation [11,12].…”
Section: Physiological Role Of Acucp and Acaox As Antioxidant Defensesupporting
confidence: 92%
“…In unicellular eukaryotes, because of their small size, which prevents any thermal gradient with their surroundings, thermogenesis has no place. Thus, the increase in activity and expression of AcAOX [11] and AcUCP [12] observed in A. castellanii mitochondria after the growth of amoeba cells at low temperature cannot be related to thermogenesis. Moreover, contrary to plant mitochondria [13], in mitochondria of A. castellanii, UCP and AOX can work together at their maximal capacities indicating a cumulative effect on oxidative Abbreviations: AA, antimycin A; AcAOX, alternative oxidase of Acanthamoeba castellanii; AcUCP, uncoupling protein of Acanthamoeba castellanii; AOX, alternative oxidase; BHAM, benzohydroxamate; BSA, bovine serum albumin; CAT, carboxyatractyloside; FFA, free fatty acids; H 2 O 2 , hydrogen peroxide; LA, linoleic acid; ROS, reactive oxygen species; UCP, uncoupling protein; DlH + , proton electrochemical gradient phosphorylation [5].…”
Section: Introductionmentioning
confidence: 93%
“…The amoeboid protozoan A. castellanii and higher plants share several common features at the level of the respiratory chain of the inner mitochondrial membrane such as the presence of an alternative ubiquinol cyanide-resistant oxidase and non-phosphorylating rotenone-insensitive internal (matricial face) and external (cytosolic face) NADH dehydrogenases [14,15]. Our previous results have shown that the activity and protein content of A. castellanii alternative oxidase is clearly increased by a growth of amoeba cells at low temperature [16]. Both, alternative oxidase and UCP, are free energy-dissipating systems which lead to the same final effect, i.e., a decrease in ATP synthesis.…”
Section: Introductionmentioning
confidence: 98%
“…Angert et al (2003) also reported low α k values (mean of 0.977, SD of 0.004) for O 2 consumption in a vadose zone in the interior of Alaska (63°49′N, 144°59′W). They attributed the low α k values to O 2 consumption by the alternative cyanide‐resistant oxidase pathway, which is more active in respiration at lower temperatures (Reyes and Jennings, 1997; Jarmuszkiewcz et al, 2001; Angert et al, 2003).…”
Section: Resultsmentioning
confidence: 99%